Income segregation and local progressive taxation : empirical evidence from Switzerland - Kurt Schmidheiny (Center for Economic Studies and ifo Institute (CESifo), 2004)
This study investigates spatial segregation of the population in fiscally decentralized urban areas. The theoretical part proposes the progressivity of local income taxes as a new explanation for income segregation. The empirical part studies how income tax differentials across municipalities in the Swiss metropolitan area of Basel affect the households? location decisions. The (multinomial) location choice of households is investigated within the framework of the random utility maximization model (RUM). The theoretical model is used to identify the household preferences applied in the RUM. The empirical results show that rich households are significantly and substantially more likely to move to low-tax municipalities than poor households.
Keywords: R23; R20; H73; H71; 330; location choice; income segregation; fiscal federalism; progressive taxation; discrete choice; Gemeindesteuer; Einkommensteuer; Steuerbelastung; Wohnstandort; Stadt-Land-Beziehung; Basel